Clinical and biomarker modifiers of vitamin D treatment response: the Multi-Ethnic Study of Atherosclerosis. Issue 3 (26th November 2021) - Hsu, Simon; Prince, David K; Williams, Kayleen; Allen, Norrina B; Burke, Gregory L; Hoofnagle, Andrew N; Li, Xiaohui; Liu, Kiang J; McClelland, Robyn L; Michos, Erin D; Psaty, Bruce M; Shea, Steven J; et al.
ABSTRACT: Background: Different 25-hydroxyvitamin D [25(OH)D] thresholds for treatment with vitamin D supplementation have been suggested and are derived almost exclusively from observational studies. Whether other characteristics, including race/ethnicity, BMI, and estimated glomerular filtration rate (eGFR), should also influence the threshold for treatment is unknown. Objectives: The aim was to identify clinical and biomarker characteristics that modify the response to vitamin D supplementation. Methods: A total of 666 older adults in the Multi-Ethnic Study of Atherosclerosis (MESA) were randomly assigned to 16 wk of oral vitamin D3 (2000 IU/d; n  = 499) or placebo ( n  = 167). Primary outcomes were changes in serum parathyroid hormone (PTH) and 1, 25-dihydroxyvitamin D [1, 25(OH)2 D] concentrations from baseline to 16 wk. Results: Among 666 participants randomly assigned (mean age: 72 y; 53% female; 66% racial/ethnic minority), 611 (92%) completed the study. The mean (SD) change in PTH was −3 (16) pg/mL with vitamin D3 compared with 2 (18) pg/mL with placebo (estimated mean difference: –5; 95% CI: –8, –2 pg/mL). Within the vitamin D3 group, lower baseline 25-hydroxyvitamin D [25(OH)D] was associated with a larger decline in PTH in a nonlinear fashion. With baseline 25(OH)D ≥30 ng/mL as the reference, 25(OH)D <20 ng/mL was associated with a larger decline in PTH with vitamin D3 supplementation (–10; 95% CI: –15, –6 pg/mL), whereas 25(OH)D of 20–30 ng/mL was not (–2; 95% CI: –6, 1 pg/mL). A segmented threshold model identified a baseline 25(OH)D concentration of 21 (95% CI: 13, 31) ng/mL as an inflection point for difference in change in PTH. Race/ethnicity, BMI, and eGFR did not modify vitamin D treatment response. There was no significant change in 1, 25(OH)2 D in either treatment group. Conclusions: Of characteristics most commonly associated with vitamin D metabolism, only baseline 25(OH)D <20 ng/mL modified the PTH response to vitamin D supplementation, providing support from a clinical trial to use this threshold to define insufficiency. This trial was registered at clinicaltrials.gov as NCT02925195.